A Systematic study of structural and electronic properties of beryllium and nitrogen co-doped stanene for optoelectronic application: A systematic study of structural and electronic properties of beryllium and nitrogen (Gadau Journal of Pure and Allied Sciences, 2024)
This paper investigates the structural and electronic properties of doped/co-doped stanene with Be and N atoms using first principles calculations. The computed lattice parameters, bond length and bond angle with van der Waals corrections (vdW-DFC09x) were found to be close to the experimental results. Band structure calculations revealed that pure stanene is a zero-band gap material with Dirac cone located at K-point and this matched very well with previous theoretical and experimental results. Be doped stanene exhibits a band gap above the Fermi level of 0.29, 0.56 and 1.1 eV for 5.6 %, 11.1 % and 16.7 % concentrations, indicating that Be doped stanene could behave as degenerate semiconductor. For N doped stanene the band-gap below the Fermi level were 0.30, 0.45 and 0.96 eV for 5.6 %, 11.1 % and 16.7 % doping concentrations. Our results show that there is transition from metallic nature as in the case of pure stanene to semiconductor for Be and N mono-doped stanene.  Additionally, Be-N co-doped stanine opens up a wider band gap in comparison with the mono doping. A band gap value of 1.24 eV was formed above the Fermi level in the case of Be-N co-doping showing p-type character. Accordingly, our findings suggested that Be-N co-doped stanene is a promising material for optoelectronic, solar and other application like Be-N co-doped graphene.
Keywords: DFT; Stanene; Co-doping; Solar cells